Âge à la ménopause naturelle à Marrakech (Maroc) et prévalence des symptômes du climatère - Mohamed Loukid; Mohamed Kamal Hilali; Cristina Bernis (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The aim of the present study is to evaluate the median age at natural menopause and the prevalence of menopausal symptoms in a sample of Moroccan women. The sample was collected in the city of Marrakech and consists of 571 women aged between the ages of 39 and 61. The median age of menopause observed by status quo method in 2001 and calculated by mean of probit analysis was 50.25 ± 6.5 years. In comparison with other studies, the median age found in Marrakech appears to be one of the oldest. It is significantly higher than those found in the Rabat city and in the Marrakech region. The discussion of this result focuses on the differences in the methodologies used in the different studies and speculates on the possibility of an increase in this age due to improvement of living conditions in a Moroccan urban environment. With regard to menopausal symptoms, the most frequent complaints are joint pain (90%), headaches (86%), and fatigue (83%). They are followed by hot flashes and problems of sexuality reported respectively by 73% and 72% of women. The prevalence of classic menopausal symptoms in our population was high compared with other studies. These relatively high percentages may be linked to the reproductive characteristics of women who are primarily housewives married at an early age.